2016
DOI: 10.1007/s13277-015-4768-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation and induction of apoptosis in RB116 retinoblastoma cells by afatinib treatment

Abstract: The present study investigates the effect of afatinib on the growth, induction of apoptosis in RB116 cells, and reduction of carcinoma growth in the mice transplanted with RB116 cells. The results from MTT assay revealed that afatinib inhibited the growth of RB116 cells in a dose-dependent manner. Proliferation of RB116 cells was reduced to 64 % on treatment with 200 μM concentration of afatinib after 48 h. Afatinib treatment of RB116 cells at 200 μM concentration induced apoptosis and necrosis in 49.7 and 9.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Previous studies reported that afatinib can inhibit cell proliferation and induce apoptosis in various types of cancer cells [2931]. To explore whether afatinib could induce apoptosis in NB cells, IMR-32, NGP, NB-19, SK-N-AS, SH-SY5Y, and LA-N-6 cells were treated with afatinib for various time points (0-16 hrs).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that afatinib can inhibit cell proliferation and induce apoptosis in various types of cancer cells [2931]. To explore whether afatinib could induce apoptosis in NB cells, IMR-32, NGP, NB-19, SK-N-AS, SH-SY5Y, and LA-N-6 cells were treated with afatinib for various time points (0-16 hrs).…”
Section: Resultsmentioning
confidence: 99%
“…We first observed growth inhibition and apoptosis in afatinib-treated H1975 and H1650 cells. Many studies prove that the TKI-induced apoptosis is caspase 3 dependent 38 , 39 , and it has been reported that afatinib could induce H1975, H1650 and RB116 cell apoptosis by activation of caspase 3 40 , 41 . Our experiments proved that afatinib dramatically increased casepase 3 activity, and pan-caspase inhibitor z-VAD-fmk could rescue the cells and decrease caspase 3 activity as well as the level of cleaved-PARP.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, there are a few studies on the use of tyrosine kinase inhibitors against retinoblastoma. Available data demonstrated good outcomes achieved in vitro with the use of afatinib, erlotinib (both are EGFR inhibitors), and imatinib (PDGFRA and PDGFRB inhibitor) [53][54][55].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%